Organization of the mitochondrial genome of Ramulus irregulatiter dentatus (Phasmatidae: Phasmatidae) - Zhang, Congfen; Guo, Xiaoqiang (Frontiers in Genetics, 2022)
Ramulus irregulatiter dentatus (R. irregulatiter dentatus) in the Phasmatidae subfamily Phasmatidae is phytophagous and majors leaves feeding pest specie, which causes severe economic losses to forests and plants. Here, we obtained the complete mitochondrial genome of R. irregulatiter dentatus, detected by Illumina next-generation sequencing. The entire mitochondrial genome is 16,060 bp in length; contained the standard set of 13 protein-coding genes, 22 transfer RNA genes (tRNAs), 2 ribosomal RNA genes (rRNAs), and a putative A+T-rich region. The base composition and codon usage were typical of Phasmatodea species. The mitochondrial gene organization (37 genes) was consistent with that of other Phasmatidae. And, a phylogenetic tree was built from the sequence information of the 13 protein-coding genes by Bayesian analyses. The newly sequenced R. irregulatiter dentatus was most closely related to the family Phasmatidae. The complete mitochondrial genome of R. irregulatiter dentatus also provides valuable molecular information for future studies on Phasmatidae insects taxonomy and a framework to unveil more of their cryptic and underestimated diversity.